Advances in the Pharmacotherapy of Periodontal and Oral Mucosal Diseases - R. Slezák; L. Ryšková; V. Paulusová; Z. Šustová; I. Berglová; V. Buchta (Czech Dental Chamber, 2012)
Introduction: There are many of drugs useful for topical or systemic treatment of diseases of periodontal tissue and oral mucous membrane. Their correct administration and efficacy depend strictly on adeqnate of information regarding their properties. Aim: The review deals with some drugs newly available in Czech Republic and related therapeutic procedures used in the treatment of periodontal and mucosal diseases. Therapeutic agents: For topical chemical inhibition of the dental plaque are dedicated octenidine, kationic antiseptic pyridine derivate, and combination of classic bis-biguanide derivate chlorhexidine with aromatic agent eugenol. As adjuvant chemotherapeutics in the treatment of periodontitis serve systems for targeted antimicrobial photodynamic therapy based on the use of photosensitizers as producers of the singlet oxygen, namely toluidine blue O and methylen blue. The source of monochromatic light for their pohotoactivation is laser device. Saturated alcohol docosanol with antiviral acitivity serves in topical therapy of labial herpes. Vanillinamide alkaloid capsaicine is selective agonist of vanilloid receptore TRPV 1 of sensitive nerves. Patch product Qutenza has been recently used for higly effective topical treatment of neuropatic pain. It could be potentially very useful agent in the treatment of some forms of atypical facial pain. Irradiation of salivary glands results in association with its dosis in the damage of various grade of the glandular parenchyma associated with postirradiative hyposialia. Cytoprotective prodrug amifostine releases active thiol after its dephosphorylation. It is recommended for the protection of the glandular parenchyma against adverse effects of antitumorous drugs and therapeutic irradiation in the region of the head and neck. Conclusion: Spectrum of therapeutic agents useful in the treatment of periodontal and mucosal diseases raises permanently. Efficacy of their application is connected with sufficient information of professionals and correct and early diagnosis of the disease, as well.